Repúblicas laicas en Europa y América: la separación de la Iglesia y el Estado en Portugal vista desde México, 1910 - 1913 (2015)
This article aims to analyze the bilateral relationship between Mexico and Portugal between 1910 and 1913 on the basis of a concrete case: reconstructing the reactions produced in Mexico by the declaration of the Portuguese Republic and, later on, the announcement of the Church-State separation, in April 1911, which was one of the core aspects of the Portuguese republican movement. It proves that the Mexican government, based on the information sent by the poet and diplomat, Balbino Davalos, who was in charge of Mexico’s businesses in Lisbon, had an ambivalent reaction towards the onset of the republican regime, and the secularization of the Portuguese state. On one hand, the change of government system was accepted and even supported, for they considered this measure would allow strengthening the relationship between both nations, since they share the same political regime and the same relationship with the Church. On the other hand, specially within the diplomatic circles and local elites, the fall of the monarchy was considered a disruption of peace, order and stability similar to that one of the Mexican revolution, that led to the end of Porfirio Diaz’s regime between 1910 and 1911; and the beginning of Francisco y Madero’s government.